Nutrient Recovery from Municipal Wastewater for Sustainable Food Production Systems: An Alternative to Traditional Fertilizers - Theregowda, Ranjani B. (Environ Eng Sci, 2019)
Traditional wastewater management uses end-of-pipe approaches to remove pollutants in wastewater before discharge. Although effective in human health protection for decades, this approach of removal and disposal requires a high investment of energy and materials and overlooks the values of the key nutrients in wastewater such as phosphorus (P). Phosphorus in wastewater comes from the human metabolites of food, resulted from crop uptakes of fertilizer that ultimately derived from phosphate rock (PR). PR, however, could be depleted in this century, which would lead to a global food crisis. To address the question whether nutrient recovery is indeed a more efficient strategy from a system perspective and provides more benefits to society, this research compares fertilizer production from struvite to the traditional commercial fertilizers (e.g., diammonium phosphate, DAP). Emergy defined as the available energy required directly and indirectly through all transformations to make a product, process, or service is the tool used for system analysis in this study. Emergy accounting provides system analysis of total resource use and whole system efficiency. The results show that struvite production uses one order of magnitude less emergy than DAP production to produce one unit of fertilizer, indicating that struvite production is a more efficient process. This research sheds light on alternative nutrient management through nutrient recovery, which may achieve economic and environmental benefits and overall higher system efficiency.